FEATURES OF THE APPLICATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS IN THE SYSTEM OF ACCOUNTING FOR INTANGIBLE ASSETS (American Journal of Business Management, Economics and Banking, 2026)
This article presents opinions on the organization of accounting in our Republic based on International Financial Reporting Standards (IFRS) and the organization of accounting for intangible assets based on the requirements of International Financial Reporting Standards, their recognition and valuation methodology.